Efeitos de sentidos em uma logomarca municipal: estudo de caso sob a ótica da análise do discurso de linha francesa - Gomes, Júnior Antonio da Silva (2015)
The logo is an essential element for distinguishing and identifying a company as well as, product or segment. From it are established various concepts of positive or negative about the brand it represents, so its structure, dissemination and maintenance follow detailed concepts for thus succeed. Many of these materialized speeches acquire such a level of expressiveness to the population that no longer simply "brands" and take upon themselves the assumption of identity and / or essence. This is the case with the logos of symbols used by federal authorities, State and Municipal. This political discourse is used indiscriminately and in large scale by public officials, disseminating discursive and ideological formations arising from your (s) representative (s). This work aims to analyze the speech of the logo of a municipality in the state of Pernambuco from the perspective of French Discourse Analysis, noting that the elements present in this system of production of meaning. The corpus chosen for this study is a municipal logo which features in its linguistic materiality, political discourse and circulated in different "media" during the governance period going from January 2005 to December 2008. This speech was collected from research and investigations in municipal archives, as well as in documents issued by the municipal government in the above reporting period. The theoretical basis of our work is the French Discourse Analysis (DA), is tying by its segments and constituent concepts such as discursive, ideological formations (ideologies), muting, subject positions, production conditions and interdiscourse, based the great documentary collection produced by Pêcheux, founder and the most important scholars of discourse analysis, but also admitted them in the Dubois conceptions, Maldidier and new reflections structured light of AD by Authier-Revuz and Orlandi. Already about the structuring concepts of practices related to advertising and propaganda regarding the logo, we launched hand to Carvalho materials, Martins, Cotrim and Citelli. We point out that after collection and corpus selection used as an analytical procedure the information described from the theoretical and methodological framework of AD, being our head north to the construction of this work. The analyzes were identified as the subject builder of political discourse (logo) excites the senses bringing out elements that are crystallized in the discursive memory of the individual viewer. In short, from the reflections on the subject matter, in line with the theoretical framework of discourse analysis it was conceivable that the logo constitutes an important discourse that circulates in and through language, which is a powerful representation mechanism, demarcation, positioning and expression of power.